Study of knowledge on Science Fair in the Minutes of BDTD and CAPES: significant aspects to the process of teaching and learning in High School (Research, Society and Development, 2020)
This article aims to analyze significant aspects with the Science Fair event in public schools in the city of Alto Alegre, Roraima (RR), from the perspective of high school students and teachers. We sought to answer the problem: What are the significant aspects with the Science Fairs event, in public schools in the city of Alto Alegre (RR), from the perspective of high school teachers and students? The methodology is exploratory, qualitative and quantitative, therefore, mixed; a bibliographic analysis was also carried out. The search was based on the databases: Brazilian Digital Library of Theses and Dissertations (BDTD) and CAPES Theses and Dissertations Catalog. As a result, we observed that the number of theses and dissertations on this topic is still very small. When the filters are made, this number decreases significantly, and when joining the four terms of the research, no related studies appears in any searched databases. Thus, it is clear that the issue of Science Fairs in the school context needs to be worked with more emphasis, as scientific production is very important and significant, considering the learning of students within schools.